The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/su11164260
|View full text |Cite
|
Sign up to set email alerts
|

Is Embodied Energy a Better Starting Point for Solving Energy Security Issues?—Based on an Overview of Embodied Energy-Related Research

Abstract: Embodied energy is termed as the total (direct and indirect) energy required to produce economic or environmental goods and services. It is different from the direct energy measurement of energy consumption. Due to the importance of energy security, it has attracted increasing attention. In order to explore whether and to what extent embodied energy can provide a more innovative approach and competitive perspective to energy security issues, 2608 relevant pieces of literature from the Web of Science core colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 81 publications
(128 reference statements)
0
6
0
Order By: Relevance
“…It is the production and transportation consumed when products and services are transferred from one region to another and the direct and indirect energy consumed by the entire link of the flow of products and services between industries or departments [16,[31][32][33][34][35]. It has the characteristics of comprehensiveness, flowability, separability, and scalability [23]. Its most outstanding value is that it can effectively reflect the actual energy dependence between countries, connecting energy and economical energy with the environment [16,36,37].…”
Section: Embodied Energy and Its Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the production and transportation consumed when products and services are transferred from one region to another and the direct and indirect energy consumed by the entire link of the flow of products and services between industries or departments [16,[31][32][33][34][35]. It has the characteristics of comprehensiveness, flowability, separability, and scalability [23]. Its most outstanding value is that it can effectively reflect the actual energy dependence between countries, connecting energy and economical energy with the environment [16,36,37].…”
Section: Embodied Energy and Its Calculationmentioning
confidence: 99%
“…Embodied energy analysis can integrate historical and offsite formation and thus provide a more systematic perspective of energy use [20]. Moreover, because of its ability to track energy consumption in the economic system, it has become a hot topic in research related to determining the impact of the economy on the environment [21][22][23][24][25][26][27]. By using trade and input-output data between countries, calculating the embodied energy flow between countries can clarify the actual energy dependence between countries [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, a key performance index for our indigenous building materials, the EE must be ascertained as an indispensable common denominator for the stimulation. It has become necessary because embodied energy can be used in more fields (identify the linkage effects of policies) and it can provide a new perspective for the study of energy-related issues [57]. Thus, it enables us to analyze energy-related issues from the perspective of the whole supply chain and the whole energy flow network, instead of based on single energy supply or a single stage of energy consumption [58][59].…”
Section: Ezema Andmentioning
confidence: 99%
“…"Complex network analysis" is also commonly used in embodied energy research (An et al, 2015;Chen and Chen, 2015;Yang et al, 2015;Sun et al, 2016;Chen et al, 2018;Liu et al, 2019;Tang et al, 2019). Chen conducted a comprehensive analysis of the abundance of literature related to embodied energy and concluded that embodied energy can provide a well-integrated perspective on energy consumption and demand, and as embodied energy has been used in academics, issues related to China have been holding a high level of attention (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%